Impact of Sesame Oil vs Chlorhexidine Mouthwash on Gingivitis: A Randomized Controlled Study (Academia Journal of Medicine, 2025)
Aim: To evaluate the effectiveness of 0.2% chlorhexidine and sesame oil (SO) in  Oil Pulling Therapy (OPT) for patients with gingivitis. Materials and methods:  75 participants were divided at random into group A- Scaling only, B- Scaling with  prescribed SO and C- Scaling with Chlorhexidine respectively. Participants were  instructed regarding the use of OPT with SO and Chlorhexidine in addition to their  regular dental hygiene regimen for 30 days. Results: The mean plaque and gingival  index in group B and C was reduced after 1 month compared to baseline scores.  Statistically significant variance showed between group A and B and group A and  C respectively. OPT decreased gingivitis and plaque after a month but group B and  C did not show significant variance. Conclusion: Because oil pulling is a domestic  remedy that assists in avoiding gum infections in nations with restricted resources,  we need to spread knowledge of it.
Keywords: Oil pulling therapy; Sesame oil, 0.2% Chlorhexidine; Gingivitis